2020
DOI: 10.1371/journal.pone.0237355
|View full text |Cite
|
Sign up to set email alerts
|

Better programmatic outcome with the shorter regimen for the treatment of multidrug-resistant tuberculosis (MDR-TB) in Guinea: A retrospective cohort study

Abstract: Setting Since August 2016, after the Ebola outbreak, the Guinean National Tuberculosis Programme and Damien Foundation implemented the shorter treatment regimen (STR) for multidrug-resistant tuberculosis (MDR-TB) in the three MDR-TB sites of Conakry. Previously, the longer regimen was used to treat MDR-TB. Objectives In a post-Ebola context, with a weakened health system, we describe the MDR-TB treatment uptake, patients characteristics, treatment outcomes and estimate the effect of using the longer versus STR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…Kamara et al found a higher success rate of 80% vs. 54% among patients treated with the shorter regimen (9-11 months) compared to the longer (18-24 months) (see appendix 3 for treatment regimens) (Kamara et al, 2022). Similar results were reported by Hassane-Harouna et al who found a successful outcome in 74% with the shorter regimen vs. 59% with the longer regimen (Hassane-Harouna et al, 2020). They also found that a higher number of patients were LFTU if treated with the longer regimen.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Kamara et al found a higher success rate of 80% vs. 54% among patients treated with the shorter regimen (9-11 months) compared to the longer (18-24 months) (see appendix 3 for treatment regimens) (Kamara et al, 2022). Similar results were reported by Hassane-Harouna et al who found a successful outcome in 74% with the shorter regimen vs. 59% with the longer regimen (Hassane-Harouna et al, 2020). They also found that a higher number of patients were LFTU if treated with the longer regimen.…”
Section: Resultssupporting
confidence: 58%
“…Adverse effects have been known to affect the proportion of patients that are LTFU (Huerga et al, 2017). The study from Guinea (Hassane-Harouna et al, 2020), where DOT was not applied, also found a higher rate of LTFU among patients on the longer treatment regime (20% vs. 8.2%) in agreement with the proposition that shorter treatment regimens will have a positive effect on the treatment default rate due to fewer adverse effects and smaller burden of pills (Schwoebel et al, 2020, Trébucq et al, 2018. The largest study (n=845) had a low rate of LTFU of 4.5% in comparison to the other studies in light of the considerable cohort size (Schwoebel et al, 2020).…”
Section: Discussionmentioning
confidence: 78%
“…The higher proportion of XDR-TB patients may have contributed to the lower success rate in that study. Reports from other countries showed a success rate ranging from 38.6% to 74.0% [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the STR studies conducted in Africa and Asia have shown impressive treatment success ranging between 80.2% and 95.5% [ 8 , 9 , 11 , 26 , 27 ]. Treatment effectiveness of STR was comparatively worse in Swaziland (70.8%) [ 10 ] and Guinea (74.0%) [ 28 ], but nevertheless much higher than treatment effectiveness of the longer regimen reported in their countries. In our study population treatment failure was the predominant reason of unfavorable treatment outcome, accounting for 17.9% of all patients.…”
Section: Discussionmentioning
confidence: 99%